Evaluation of the antibacterial activity of Camellia sinensis (green tea) extract against Streptococcus mutans - Thayalini, T.; Mufeena, M.M.F.; Wathooth, A.M.A.; Ashra, M.R.F.; Gnanakarunyan, T.J.; Mafras, F.S.S.; Jayatilake, J.A.M.S.; Ramachandran, R. (Sri Lanka Society For Microbiology, 2024)
Introduction and Objectives: Streptococcus mutans is a common oral commensal responsible for dental caries and systemic infections in compromised patients. Green tea (Camellia sinensis) is a popular beverage which contains catechins with antibacterial properties. The aim of this study was to evaluate the antibacterial activity of green tea extract against S. mutans isolated from dental caries. Methods: Camellia sinensis powder (gun powder 1) was obtained from a tea factory in the Central Province, Sri Lanka. Ethanolic extract of C. sinensis was prepared and used to screen the antibacterial activity. A total of 85 isolates of S. mutans were used in the study. This included 84 isolates collected from caries lesions of patients attending the Dental Clinic, Teaching Hospital Jaffna between September to October 2023 and the standard strain of S. mutans (ATCC 700610). There were 18 erythromycin resistant and 14 clindamycin resistant S. mutans isolates within the 84 clinical isolates. Erythromycin (15 μg) and distilled water were used as positive and negative controls. Well diffusion method was used to check the antibacterial activity. Accordingly, after inoculation of S. mutans onto Mitis salivarious agar medium, 9cm wells were cut, loaded with tea extract (2.5 mg/mL) and controls before incubating at 37 °C at 5-10% CO2 incubator. Diameter of the zone of inhibition (ZOI) was measured after 24 hours of incubation. Results: Ethanolic green tea extract demonstrated a 13.08% yield and inhibited all 84 clinical isolates with the diameter of ZOI ranging from 19±3.2 mm to 32.67±3.2 mm, demonstrating an anti-bacterial potential. Mean ZOI against standard S. mutans strain (ATCC 700610) was 29±0.3 mm. Erythromycin and clindamycin resistant isolates were also inhibited by green tea extract with mean diameters of ZOI 21.92+3.27 mm and 22.12±3.61 mm respectively. Conclusions: Sri Lankan green tea showed anti-bacterial activity against S. mutans including the isolates that are resistant to erythromycin and clindamycin in-vitro. Hence, the green tea extract could serve as a potential ingredient in the formulation of oral hygiene products after some subsequent investigations.
Keywords: Dental caries; Streptococcus mutans; Green tea